2016
DOI: 10.1007/s11661-016-3704-3
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic Analysis of Nucleation at Hardness Indentations in High-Purity Aluminum

Abstract: Nucleation at Vickers hardness indentations has been studied in high purity aluminum cold rolled 12%. Electron channeling contrast was used to measure the size of the indentations and to detect nuclei, while electron backscattering diffraction was used to determine crystallographic orientations. It is found that indentations are preferential nucleation sites. The crystallographic orientations of the deformed grains affect the hardness and the nucleation potentials at the indentations. Higher hardness gives inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
(35 reference statements)
1
7
0
Order By: Relevance
“…It can be seen that the Vickers hardness indentation created a deformation zone, where sharp changes in orientations are seen in particular along the symmetry lines of the indentation. This is in agreement with earlier destructive experimental characterization and simulations 17 19 20 . After annealing at 275 °C for 10 min, nucleation occurs in the gauge volume of the sample in several locations near the indentation tip.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…It can be seen that the Vickers hardness indentation created a deformation zone, where sharp changes in orientations are seen in particular along the symmetry lines of the indentation. This is in agreement with earlier destructive experimental characterization and simulations 17 19 20 . After annealing at 275 °C for 10 min, nucleation occurs in the gauge volume of the sample in several locations near the indentation tip.…”
Section: Resultssupporting
confidence: 93%
“…A starting material with large grains (500 μm–7 mm) was prepared by annealing at 550 °C for 24 h. The starting material was then cold rolled to 12% reduction in thickness, after which a sample of size 6.0 × 4.0 × 1.3 mm 3 was mechanically cut and the plane formed by the rolling direction (RD) and transverse direction (TD) was electro polished to remove surface damage. Hardness indentations were made on the RD-TD plane with a Vickers diamond indenter of pyramidal shape with a square base and an angle of 136° between opposite faces using a load of 500 g. A previous investigation using exactly these experimental conditions has shown that nucleation preferentially occurs near hardness indentations in grains with higher average hardness 17 . For the present experiment a large grain with orientation {3-1-1} <215>, proven to have high nucleation probability, was chosen.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this, we can use the Vickers hardness principle to measure the resistance of the different samples; according to the following relation 14 15 : …”
Section: Microstructure Characterization Of the Steel 316l And The Effect Of The Welding Energymentioning
confidence: 99%
“…Furthermore the increase of cube texture in sheet occurs during recrystallization of rolled sheet wherein the recrystallization nuclei are found in the high GND regions due to strain gradients. To examine this effect, the occurrence of recrystallized grains after Vickers indentation of 12 % pre-rolled sheet of nominally pure aluminum of mm-sized grains were assessed as function of orientation by Xu et al [12]. For the (311) [215] orientation, the indent shape had bulged out; that is sides were convex indicating that the crystal along the indent interface was pushing up along the indenter faces from the original surface plane.…”
Section: Multiple Slip Effects In Aluminum Single Crystalsmentioning
confidence: 99%